Caring for Nature but Marginalizing Women: A Study of Ecofeminism in The Children Drama Script “Kerajaan Burung” By Saini Km - Eka Yusriansyah; Nasrullah Nasrullah; Awang Azman Awang Pawi (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
“Kerajaan Burung” is a drama script about children written by Saini KM which won a children drama script writing contest in 1980. This drama script was popular to be performed by many children theatre community since it was published firstly due to ecology pedagogical values. Besides its values, the drama script has hidden ecofeminism discourses. This research aimed to investigate those discourses. This research was descriptive qualitative research which applies reading, noting, and data card techniques in collecting the data. The theory of ecofeminism has been applied in analyzing the patriarchal perspective of anthropocentrism toward nature and women. The data of the research were words, sentences, dialogues, performance explanations (didaskali), and discourses related to ecofeminism. The source of the research data was the drama script “Kerajaan Burung” written by Saini KM. The analysis results showed that literary work written by male writers which talk about nature conservation cannot be freed by gender bias about ecology. The naming of the main character, Kiku, which is not followed by detailed characterization causes selection of the actress in theatre performances. This finding affirmed the idea that responsibility toward environmental damage and nature conservation is women's duty. Women are people who are often mocked by the patriarchal system applied in society.